If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 54 = (17x + 3) + (25x + 9) Reorder the terms: 54 = (3 + 17x) + (25x + 9) Remove parenthesis around (3 + 17x) 54 = 3 + 17x + (25x + 9) Reorder the terms: 54 = 3 + 17x + (9 + 25x) Remove parenthesis around (9 + 25x) 54 = 3 + 17x + 9 + 25x Reorder the terms: 54 = 3 + 9 + 17x + 25x Combine like terms: 3 + 9 = 12 54 = 12 + 17x + 25x Combine like terms: 17x + 25x = 42x 54 = 12 + 42x Solving 54 = 12 + 42x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42x' to each side of the equation. 54 + -42x = 12 + 42x + -42x Combine like terms: 42x + -42x = 0 54 + -42x = 12 + 0 54 + -42x = 12 Add '-54' to each side of the equation. 54 + -54 + -42x = 12 + -54 Combine like terms: 54 + -54 = 0 0 + -42x = 12 + -54 -42x = 12 + -54 Combine like terms: 12 + -54 = -42 -42x = -42 Divide each side by '-42'. x = 1 Simplifying x = 1
| 20=(8x+4)+(9x+12) | | 10v+7=8(2u-4)-9 | | 6x+2=8x+14 | | 4(x+1)=8 | | 2p-1=-4p-19 | | (2y-5)-8+y=5 | | 80=(x+9)+(6x-6) | | x^2-42xy-343y^2=0 | | 48=(14x+4)+(24x+2) | | 2b^2+7b=15 | | 2(4p+8)=128 | | x^2+3x-7=0 | | x^2-98=0 | | 2x^2-13x-7=0 | | 4(n+1)+2n=22 | | 3x^2+22x=-40 | | 5x-4=4-3x | | 9-2y=15-8y | | 5y+3=13 | | 2f=f+3 | | 2+2x=-10+5x | | -2x+8y=12 | | -9+2(4g-7)=-12 | | 3y-5=y-9 | | 3m+1=7m-15 | | 3(8-a)=(90-3a) | | 3(8-a)=18(5-3a) | | w+9=5w+5 | | 5y+7=7y-3 | | 10w+19+3w=6(9+w)-14 | | 3x(8-a)=18x(5-3a) | | 5x+2y=-17 |